Accompagner la réflexivité sur l’expérience : une médiation cognitive et socio-affective vers l’apprentissage - Laurence Durat; Dominique Kern (Activités)
Our goal is to support the cross-analysis of experience between professionals and researchers, in order to ensure that the experience is constructive when retrieved. Positioning ourselves within the framework of ergonomic psychology’s activity analysis, we look at the conditions for accessing a past professional experience and we question the possibility of returning to the meaning attributed to this experience. After studying the contributions and limits of reflexivity-based processes, we present a case study. This case took place during the professional career of an older employee and we endeavour to propose a framework of analysis that serves reflexivity, using the critical incident technique and a co-analysis device that questions cognitive and socio-affective accessibility to lived experience. The main result is, indeed, that access to experience is both possible and desirable, as co-analysis allows certain conditions to be reconfigured in the sense of experience from a development perspective.